The Effects of Enzymes, Species, and Storage of Raw Material on Physicochemical Properties of Protein Hydrolysates from Whitefish Heads - Jannicke Fugledal Remme; Sigurd Korsnes; Stine Steen; Rachel Durand; Kristine Kvangarsnes; Janne Stangeland (Marine Drugs, 2023)
The rest raw materials of whitefish have great potential for increased utilisation and value creation. Whitefish heads have a high protein content and should be considered a healthy protein source for the growing population’s demands for sustainable protein. In this study, the heads of four different species of whitefish were processed via enzymatic hydrolysis, namely cod (Gadus morhua), cusk (Brosme bromse), haddock (Melanogrammus aeglefinus), and saithe (Pollachius virens), using three commercially available enzymes. Trials were conducted after 0, 3, and 6 months of the frozen storage of heads. A proximate analysis, molecular weight distribution, and protein solubility were evaluated for each of the products. The results show that, although the enzymatic hydrolysis of rest raw materials from different species of whitefish yielded products of slightly different characteristics, this process is viable for the production of high-quality protein from cod, cusk, haddock, and saithe heads. Six months of frozen storage of heads had a minimal effect on the yield and proximate composition of hydrolysates.